การพัฒนาทักษะการอ่านออกเสียงสะกดคำศัพท์ภาษาอังกฤษโดยใช้ชุดฝึกทักษะ การอ่านสะกดคำโฟนิกส์ Phonics สำหรับชั้นประถมศึกษาปีที่ 2 - รอดวินิจ, พิพัฒนเขตต์; ข่าสะโปน, สมควร; กรมน้อย, อานันท์; พันทะลี, พระณัฐวุฒิ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 3 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 3 : กันยายน - ธันวาคม 2567, 2024)
This research aims to: (1) compare the English word decoding and pronunciation skills of students using the Phonics-based word decoding skill development kit, and (2) examine students' satisfaction with the development of their English word decoding and pronunciation skills using the Phonics-based. The target group consisted of 20 Grade 2 students from Ban Nonchai Municipal School. The study employed an experimental research design. The research instruments included: (1) a Phonics-based word decoding skill development kit, and (2) pre-test and post-test assessments to measure English word decoding and pronunciation skills. Data analysis was conducted using descriptive statistics, including mean and standard deviation, as well as inferential statistics through the Paired Samples t-test. The findings of the study revealed that: 1) The students' English word decoding and pronunciation skills improved significantly after using the Phonics-based word decoding skill development kit, with a statistical significance level of .05. 2) The students' satisfaction with the development of their English word decoding and pronunciation skills through the Phonics-based kit was at a high level.